Last minute policies and the incumbency advantage - Elena Manzoni; Stefan P. Penczynski (University of Mannheim, Department of Economics, 2014)
This paper models a purely informational mechanism behind the incumbency advantage. In a two-period electoral campaign with two policy issues, a specialized incumbent and an unspecialized, but possibly more competent challenger compete for election by voters who are heterogeneously informed about the state of the world. Due to the asymmetries in government responsibility between candidates, the incumbent's statement may convey information on the relevance of the issues to voters. In equilibrium, the incumbent sometimes strategically releases his statement early and thus signals the importance of his signature issue to the voters. We find that, since the incumbent's positioning on the issue reveals private information which the challenger can use in later statements, the incumbent's incentives to distort the campaign are decreasing in his quality, as previously documented by the empirical literature. The distortions arising in equilibrium are decreasing in the incumbent's effective ability; however, the distortions may be increasing in the incumbent's reputation of expertise on his signature issue.
urn:nbn:de:bsz:180-madoc-371899
Keywords: D72; D82; D60; 330; Incumbency advantage; electoral competition; information revelation; agenda setting